Maternal Serum Ferritin, C-Reactive Protein, and Procalcitonin Levels for Predicting Subclinical Intra-Amniotic Infection in Preterm Premature Rupture of Membrane - Balsam N. Nahedh; Mahdi M. Shalal (مجلة كلية الطب)
Background: The preterm premature rupture of the membrane is linked to various perinatal problems, including chorioamnionitis.